2018
DOI: 10.3390/agriculture8110168
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Urban Agriculture: Vegetable Production on Green Roofs

Abstract: The practice of producing vegetables on green roofs has been gaining momentum in recent years as a method to facilitate agricultural sustainability in urban areas. Rooftop gardens are becoming an important part of the recent rejuvenation of urban agriculture, and offers alternative spaces to grow vegetable products for urban markets. Green roofs create spaces for the production of vegetable crops, which then generate opportunities for integrating agriculture into urban communities. However, vegetable productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 20 publications
0
62
0
4
Order By: Relevance
“…Green roof substrates are low in organic matter so nutrient supplementation is often required for urban rooftop food production. Selective treatments of synthetic fertilizers may improve yields, but caution is required to prevent excessive stormwater runoff contamination (Walters and Midden 2018;Whittinghill et al 2016).…”
Section: Long-term Dynamicsmentioning
confidence: 99%
“…Green roof substrates are low in organic matter so nutrient supplementation is often required for urban rooftop food production. Selective treatments of synthetic fertilizers may improve yields, but caution is required to prevent excessive stormwater runoff contamination (Walters and Midden 2018;Whittinghill et al 2016).…”
Section: Long-term Dynamicsmentioning
confidence: 99%
“…The depth of the substrate layer is also crucial to the success of the green roof; being accepted that plant physiological responses and growth will increase with deeper substrates. However, the greater vegetable crops production potential on green roofs is given by an extensive cultivation bed from 0.08 to 0.15 m high at maximum, due to weight load restrictions for most buildings [9]. Nevertheless, this limit may be adjusted according to the substrate physical properties and the crop selected.…”
Section: David Publishingmentioning
confidence: 99%
“…At the same time, the knowledge about which species are best suited to this cultivation system and their proper management is essential to achieve the desired goals. Research reported by Walters and Midden [9] has shown that lettuce can be produced effectively in a green cover medium with enough nutrient and moisture. Whittinghill et al [13], on the other hand, reported that crops with deeper root system, as tomatoes, require more rigorous monitoring of the fertility and humidity levels of the root environment, as well as deeper knowledge about the basic characteristics of the substrate to be able to properly manage it.…”
Section: David Publishingmentioning
confidence: 99%
“…However, nowadays, UA is practiced more for social, cultural, and environmental reasons than provisioning [38][39][40]. The forms of UA are community gardens, urban farms, edible school gardens, and roof farms [41][42][43]. UA provides people with many nature contact opportunities.…”
Section: Introductionmentioning
confidence: 99%